Profibrotic role of WNT10A via TGF-β signaling in idiopathic pulmonary fibrosis. Issue 1 (December 2016) - Oda, Keishi; Yatera, Kazuhiro; Izumi, Hiroto; Ishimoto, Hiroshi; Yamada, Sohsuke; Nakao, Hiroyuki; Hanaka, Tetsuya; Ogoshi, Takaaki; Noguchi, Shingo; Mukae, Hiroshi
Abstract Background WNT/β-catenin signaling plays an important role in the pathogenesis of idiopathic pulmonary fibrosis (IPF); however, the role of WNT10A via transforming growth factor (TGF)-β signaling remains unclear. Methods We evaluated the expression of WNT10A and TGF-β in bleomycin (BLM)-treated mice and the interactions between TGF-β or BLM and WNT10A in vitro. Additionally, we investigated IPF patients who underwent video-assisted thoracoscopic surgery to determine whether the WNT10A expression is related to the survival. Results Increased WNT10A and TGF-β expressions were noted in the BLM-treated mice. Real-time PCR and luciferase reporter assays demonstrated the levels of WNT10A and collagen in the fibroblasts cells to increase after TGF-β administration. Conversely, WNT10A siRNA treatment inhibited the synthesis of collagen in the transfected fibroblasts cells. A Kaplan-Meier survival analysis demonstrated a tendency toward a poor survival among the IPF patients with a WNT10A-positive expression compared to those with a negative expression (Hazard ratio 5.351, 95 % CI 1.703-16.82;p  = 0.0041). An overexpression of WNT10A was found to be significantly predictive of an acute exacerbation of IPF (AE-IPF) (Odds ratio 13.69, 95 % CI 1.728-108.5;p  = 0.013). Conclusions WNT10A plays an important role in the pathogenesis of IPF via TGF-β activation and it may also be a sensitive predictor for the onset of an AE-IPF.